Method for manufacturing electrolytic capacitor with electrically conductive polymer
Patent Information
- Application Number
- CN202580023806.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-02-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0042]根据本公开的方法,能够提供一种电容器的制造方法,其包括使导电性高分子含有液以多阶段浸渗于电容器元件中,在所述方法中能够在各浸渗阶段得到充分的特性改善效果。
Smart Images

Figure CN122996492A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing an electrolytic capacitor with conductive polymers. Background Technology
[0002] (Electrolytic capacitors made of conductive polymers)
[0003] Previously, solid electrolytic capacitors using conductive polymer compounds as solid electrolytes were known. Such capacitors exhibit low ESR and excellent low-temperature characteristics. Furthermore, by using a solid, heat-resistant, and highly conductive polymer as the electrolyte, such capacitors can provide high reliability.
[0004] To improve the properties of electrolytic capacitors containing conductive polymers (conductive polymer compounds), the use of various additives was investigated.
[0005] Patent Document 1 describes a method for manufacturing an electrolytic capacitor, which includes the following steps: after impregnating a dispersion of a conductive polymer into a capacitor element, performing at least one drying operation; after forming a conductive polymer layer on the capacitor element, impregnating the capacitor element with a high-boiling-point organic solvent with a boiling point of 150°C or higher, or impregnating the capacitor element with a solution containing 20% by mass or more but less than 100% by mass of a high-boiling-point organic solvent with a boiling point of 150°C or higher, and performing at least one drying operation.
[0006] Patent Document 2 describes a method for manufacturing a solid electrolytic capacitor, which includes the following steps: forming a dielectric oxide coating on the surface of an electrode body made of a porous valve metal; then, immersing the electrode body in a solution for forming a metal oxide semiconductor layer with a concentration of less than 30% by weight, forming a metal oxide semiconductor layer as a conductive pre-coating on the dielectric oxide coating, performing this formation process up to twice; then, alternatingly repeating the steps of immersing the electrode body in a solution containing heterocyclic compounds and their derivatives, and immersing the electrode body in a solution containing an oxidant and a dopant with an electrode potential higher than the oxidation potential of the heterocyclic compounds and their derivatives, to form a conductive polymer electrolyte layer by chemical oxidative polymerization.
[0007] Patent Document 3 describes a method for manufacturing a capacitor having a process of forming a solid electrolyte layer on the surface of a dielectric layer, and describes the following: a conductive polymer solution containing a π-conjugated conductive polymer, a polyanion and a solvent is coated on the dielectric layer of the aforementioned capacitor substrate, and dried to form a conductive polymer film. This film-forming process is repeated two or more times. The conductive polymer solution used in the second and at least one subsequent film-forming process is a high-viscosity solution with a higher viscosity than the conductive polymer solution used in the first film-forming process.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2014-82392
[0011] Patent Document 2: Japanese Patent Application Publication No. 9-213575
[0012] Patent Document 3: Japanese Patent Application Publication No. 2010-87401 Summary of the Invention
[0013] The problem the invention aims to solve
[0014] When impregnating a capacitor element with a conductive polymer-containing liquid (e.g., a dispersion), multiple impregnation stages (e.g., two stages) can improve capacitor characteristics compared to a single impregnation stage with the same total amount of conductive polymer. However, in existing methods, the improvement in capacitor characteristics obtained at each impregnation stage is sometimes insufficient when impregnating the capacitor element with a dispersion containing conductive polymer in multiple stages.
[0015] The purpose of this invention is to provide a method for manufacturing a capacitor, which includes impregnating a capacitor element with a conductive polymer-containing liquid in multiple stages, wherein sufficient characteristic improvement can be obtained at each impregnation stage in the method.
[0016] Solution for solving the problem
[0017] The aforementioned problems of this disclosure can be solved by the following inventive methods of this disclosure.
[0018] <Method 1>
[0019] A method for manufacturing an electrolytic capacitor, wherein the electrolytic capacitor has an anode foil and a cathode foil with an oxide coating formed on their surfaces, and a solid electrolyte portion comprising a conductive polymer is present in the gap between the anode foil and the cathode foil, the method comprising:
[0020] (i) Provides a capacitor element having an anode foil and a cathode foil having an oxide coating formed on their surfaces;
[0021] (ii) A liquid containing a first conductive polymer with an organic solvent having a boiling point or decomposition temperature of 150°C or higher, at a content of 15% by mass or less, is impregnated into the aforementioned capacitor element, and dried to form a solid electrolyte precursor in the gap between the aforementioned anode foil and the aforementioned cathode foil; and
[0022] (iii) The capacitor element containing a second conductive polymer containing an organic solvent with a boiling point or decomposition temperature of 150°C or higher at a content of 15% by mass or more is impregnated in the aforementioned capacitor element in which the aforementioned solid electrolyte precursor is formed, and then dried to form a solid electrolyte in the gap between the aforementioned anode foil and the aforementioned cathode foil.
[0023] <Method 2>
[0024] According to the method of method 1, the aforementioned first conductive polymer containing liquid contains 2 to 15% by mass of the aforementioned organic solvent with a boiling point or decomposition temperature of 150°C or higher, and / or the aforementioned second conductive polymer containing liquid contains 15 to 45% by mass of the aforementioned organic solvent with a boiling point or decomposition temperature of 150°C or higher.
[0025] <Method 3>
[0026] According to the method of method 1 or 2, the aforementioned second conductive polymer containing liquid contains more than 20% by mass of the aforementioned organic solvent with a boiling point or decomposition temperature of 150°C or higher.
[0027] <Method 4>
[0028] According to any one of methods 1 to 3, the aforementioned organic solvent with a boiling point or decomposition temperature of 150°C or higher comprises at least one selected from glycerol, diglycerol, polyglycerol, ethylene glycol, diethylene glycol, polyethylene glycol, and derivatives thereof.
[0029] <Method 5>
[0030] According to any one of the methods 1 to 4, the content of conductive polymer in the first conductive polymer containing liquid and the second conductive polymer containing liquid is 0.5 to 5 by mass, respectively.
[0031] <Method 6>
[0032] According to any one of methods 1 to 5, the conductive polymer contained in the aforementioned first conductive polymer containing liquid and the aforementioned second conductive polymer containing liquid is polythiophene and its derivatives.
[0033] <Method 7>
[0034] According to any one of methods 1 to 6, the aforementioned first conductive polymer containing liquid and the aforementioned second conductive polymer containing liquid both contain microparticles composed of a conductive polymer compound and optional dopants.
[0035] <Method 8>
[0036] According to the method of method 7, the aforementioned dopant is polystyrene sulfonic acid.
[0037] <Method 9>
[0038] The method according to any one of methods 1 to 8, wherein the aforementioned electrolytic capacitor is a solid electrolytic capacitor.
[0039] <Method 10>
[0040] The method according to any one of methods 1 to 9 further includes: impregnating a liquid substance between the aforementioned anode foil and the aforementioned cathode foil of the capacitor element having the aforementioned solid electrolyte portion.
[0041] The effects of the invention
[0042] According to the method disclosed herein, a method for manufacturing a capacitor can be provided, comprising impregnating a capacitor element with a conductive polymer-containing liquid in multiple stages, wherein sufficient characteristic improvement effects can be obtained at each impregnation stage in the method. Attached Figure Description
[0043] Figure 1a This is a cross-sectional schematic diagram of an electrolytic capacitor according to one embodiment of the present disclosure.
[0044] Figure 1b This is a perspective view of a capacitor element according to one embodiment of the present disclosure.
[0045] Figure 2 This is a schematic diagram of the cross-section of the main parts of an electrolytic capacitor.
[0046] Figure 3 This is a graph showing the capacity increase factor of the respective embodiments and comparative examples.
[0047] Figure 4 This is a graph showing the ESR reduction factor for each of the embodiments and comparative examples. Detailed Implementation
[0048] <<Electrolytic Capacitors>>
[0049] The present invention discloses a method for manufacturing an electrolytic capacitor, wherein the electrolytic capacitor has an anode foil with an oxide coating formed on its surface and a cathode foil, and a solid electrolyte portion containing a conductive polymer is present in the gap between the anode foil and the cathode foil. The method includes:
[0050] (i) Provides a capacitor element having an anode foil and a cathode foil having an oxide coating formed on their surfaces;
[0051] (ii) Impregnating a capacitor element with a first conductive polymer containing less than 15% by mass of an organic solvent with a boiling point or decomposition temperature of 150°C or higher, followed by drying, to form a solid electrolyte precursor in the gap between the anode foil and the cathode foil; and
[0052] (iii) A liquid containing a second conductive polymer containing an organic solvent with a boiling point or decomposition temperature of 150°C or higher at 15% by mass is impregnated into a capacitor element having a solid electrolyte precursor, and then dried to form a solid electrolyte in the gap between the anode foil and the cathode foil.
[0053] By including additives (organic solvents with boiling points or decomposition temperatures above 150°C) in the conductive polymer-containing liquid, the characteristics of the resulting capacitor can be improved. While not intended to be theoretically definitive, it is believed that such additives added to the conductive polymer-containing liquid promote the proper arrangement (and rearrangement) of the conductive polymers and / or conductive polymer-containing particles impregnated in the capacitor element, resulting in improved capacitor characteristics.
[0054] When a conductive polymer containing liquid (especially a dispersion) is impregnated into a capacitor element, the capacitor characteristics can be improved by impregnating it in multiple stages compared to impregnating it in one stage with the same total amount of conductive polymer.
[0055] In existing methods, the improvement in capacitor characteristics obtained in each stage of such multi-stage impregnation is sometimes insufficient.
[0056] The inventors of this application have discovered that by optimizing the amount of additives in the liquid containing each conductive polymer used for multi-stage impregnation, sufficient property improvement can be achieved at each impregnation stage.
[0057] That is, in this invention, the first conductive polymer containing liquid contains 15% by mass or less of an organic solvent with a boiling point or decomposition temperature of 150°C or higher as an additive, and the second conductive polymer dispersion contains 15% by mass or more of an organic solvent with a boiling point or decomposition temperature of 150°C or higher as an additive, thereby achieving sufficient property improvement effect in each impregnation stage.
[0058] In particular, according to the present invention, by keeping the concentration of the organic solvent with a boiling point or decomposition temperature of 150°C or higher, which is used as an additive in the first impregnation, at 15% by mass or less, the capacity increase rate can be maximized. Furthermore, according to the present invention, by keeping the concentration of the organic solvent with a boiling point or decomposition temperature of 150°C or higher, which is used as an additive in the second impregnation, at 15% by mass or more, the ESR reduction effect can be maximized.
[0059] While not intended to be theoretically definitive, it is believed that by setting the additive dosage used in the first impregnation to 15% by mass or less, the effects of the additive (neutralizing the hydrophobicity of the conductive polymer and promoting impregnation) can be obtained, and the impregnation of the conductive polymer into the capacitor element due to the presence of the additive itself can be suppressed. In particular, by relatively reducing the additive dosage used in the first impregnation, adequate porosity can be ensured within the capacitor element, allowing space for the conductive polymer-containing liquid to enter during the second impregnation, and ensuring a certain level of conductivity. Furthermore, it is believed that by setting the additive dosage used in the second impregnation to 15% by mass or more, the rearrangement of conductive polymers (especially their particles) in the solid electrolyte precursor already formed in the capacitor element and the newly impregnated conductive polymers (especially their particles) to form the solid electrolyte is promoted, thereby improving capacitor characteristics.
[0060] According to the present invention, by setting the concentration of the organic solvent with a boiling point or decomposition temperature of 150°C or higher used in the first impregnation to 15% by mass or less, and setting the concentration of the organic solvent with a boiling point or decomposition temperature of 150°C or higher used in the second impregnation to 15% by mass or more, when the conductive polymer in the element is the same, the conductive polymer film exists stably compared with the production by one impregnation, thereby suppressing the deviation of characteristics and enabling stable production. Moreover, by dividing the liquid into two parts, the conductive polymer in the liquid is less than that in the liquid used in the first impregnation, thereby suppressing the aggregation of conductive polymer and extending the service life of the dispersion.
[0061] Exemplary embodiments of the present invention will be described in more detail with the help of the accompanying drawings. It should be noted that these drawings and exemplary embodiments do not limit the present invention. The drawings are schematic diagrams and are not necessarily drawn to scale.
[0062] <Construction of Electrolytic Capacitor 1 in the Embodiment>
[0063] Figure 1a and Figure 1b This diagram is shown to illustrate the electrolytic capacitor 1 of the embodiment. Figure 1a This is a cross-sectional view of electrolytic capacitor 1. Figure 1bThis is a three-dimensional view of capacitor element 20.
[0064] Figure 2 This is a cross-sectional view of the main parts shown to illustrate the main parts of the electrolytic capacitor 1 in the embodiment.
[0065] The electrolytic capacitor 1 in this embodiment is a wound electrolytic capacitor, such as... Figure 1a As shown, it has a bottom cylindrical metal housing 10, a capacitor element 20, and a sealing member 40.
[0066] The bottom portion of the metal housing 10 is approximately circular, and a valve (not shown) is located near the center. This allows the valve to rupture and release the internal pressure to the outside when the internal pressure rises. The side portions of the metal housing 10 are erected vertically from the outer edge of the bottom portion. The opening of the metal housing 10 is sealed by a sealing member 40, and the two leads 29 and 30 of the capacitor element 20 are led out to the outside through a through hole provided in the sealing member 40.
[0067] The capacitor element 20 is housed inside the metal casing 10, as shown in Figure 1(b) and Figure 2 As shown, it includes an anode foil 21, a cathode foil 23, and a separator 25 disposed between the anode foil 21 and the cathode foil 23. The anode foil 21 and the cathode foil 23 overlap and are wound together with the separator 25 in between.
[0068] exist Figure 2 In this configuration, the anode foil 21 and the cathode foil 23 each have an oxide coating (dielectric layer) 22 and 24 on their surfaces, respectively. A solid electrolyte composed of conductive polymer compound / dopant particles 26 is disposed in contact with the oxide coating 22 on the surface of the anode foil 21, forming a solid electrolyte section. Furthermore, in Figure 2 In this method, a liquid substance 27 containing a liquid substance is introduced between the anode foil 21 and the cathode foil 23. The liquid substance 27 exists in such a way that it surrounds the solid electrolyte composed of a conductive polymer compound 26.
[0069] <<Methods for Manufacturing Capacitors>>
[0070] The method for manufacturing the capacitor of the present invention is as follows:
[0071] A method for manufacturing an electrolytic capacitor, wherein the electrolytic capacitor has an anode foil with an oxide coating formed on its surface and a cathode foil, and a solid electrolyte portion comprising a conductive polymer is present in the gap between the anode foil and the cathode foil, the method comprising:
[0072] (i) Providing a capacitor element having an anode foil and a cathode foil having an oxide coating formed on their surfaces (capacitor element providing process);
[0073] (ii) The first conductive polymer containing an organic solvent with a boiling point or decomposition temperature of 150°C or higher is impregnated into the capacitor element at a mass percentage of less than 15% and dried to form a solid electrolyte precursor in the gap between the anode foil and the cathode foil (first impregnation step).
[0074] (iii) The second conductive polymer containing more than 15% by mass of an organic solvent with a boiling point or decomposition temperature of more than 150°C is impregnated into a capacitor element having a solid electrolyte precursor, and dried to form a solid electrolyte in the gap between the anode foil and the cathode foil (second impregnation step).
[0075] The following describes each step of the manufacturing method.
[0076] <Capacitor Component Supply Process>
[0077] (i) In the capacitor element supply process, a capacitor element having an anode foil and a cathode foil having an oxide coating formed on their surfaces is provided.
[0078] To illustrate step (i), firstly, aluminum foil is provided as an anode foil 21. After roughening the surface of the aluminum foil through an expansion process, a specified voltage of 2V to 500V is applied to the roughened surface of the aluminum foil to perform a chemical conversion treatment, thereby forming an oxide coating 22 on the surface of the aluminum foil. Then, a capacitor element is fabricated having an anode foil 21 with an oxide coating 22, a cathode foil 23, and a separator 25 disposed between the anode foil 21 and the cathode foil 23 (see Figure 1(b)). Specifically, the anode foil 21, which has an uneven surface (rough surface) and an oxide coating 22 formed on the uneven surface, and the cathode foil 23, which has an uneven surface, are overlapped and wound together through the separator 25, thereby fabricating a capacitor element 20. At this time, a lead 30 is connected to the anode foil 21, and a lead 29 is connected to the cathode foil 23.
[0079] Next, the capacitor element 20 is immersed in the chemical conversion solution in the chemical conversion solution bath, and a specified voltage (e.g., 100V) is applied between the lead 30 on the anode side and the chemical conversion solution for 5 minutes. This operation can repair oxide coating defects present at the end of the anode foil 21 and sometimes present on the surface.
[0080] As a chemical conversion solution, an aqueous solution of adipic acid, ammonium adipicate, boric acid, ammonium borate, phosphoric acid, ammonium dihydrogen phosphate, ammonium hydrogen phosphate, ammonium phosphate, ammonium glutarate, ammonium azelaate, ammonium tartrate, ammonium sebate, ammonium heptaate, ammonium octanoate, decanedicarboxylic acid, decanedicarboxylic acid ammonium, long-chain dicarboxylic acid, long-chain dicarboxylic acid ammonium, etc. can be used.
[0081] <Anode foil>
[0082] The capacitor disclosed herein comprises an anode foil having an oxide coating formed on its surface.
[0083] The anode foil can be formed from valve metals such as aluminum, tantalum, and niobium.
[0084] The anode foil has an oxide coating on its surface. For example, an oxide coating can be formed on the surface of the anode foil by roughening through etching based on known methods and subsequent chemical conversion treatment.
[0085] <Cathode foil>
[0086] The capacitor disclosed herein includes a cathode foil.
[0087] The cathode foil can be formed from valve metals such as aluminum, tantalum, and niobium, just like the anode foil. The cathode foil can also be formed from an aluminum alloy containing copper.
[0088] An oxide coating can also be formed on the surface of the cathode foil. For example, the surface of the cathode foil can be roughened by etching, similar to that of the anode foil, and then an oxide coating can be formed by natural oxidation. Alternatively, the cathode foil can be chemically converted at a desired voltage (e.g., 2V) to form an oxide coating.
[0089] <Separator>
[0090] The capacitor disclosed herein may include a separator. The separator is disposed between the anode foil and the cathode foil.
[0091] As a separator, it is preferable to use a separator made of synthetic resins such as cellulose fibers with good chemical compatibility with conductive polymer particles and water-soluble polymers, or nylon, PET, and PPS with excellent heat resistance. For example, heat-resistant cellulose paper and heat-resistant flame-retardant paper can be used. More specifically, as separators, examples include cellulose and its blends such as kraft paper, Manila hemp, Spanish grass, hemp fiber, and rayon; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, and their derivatives; polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins; polyamide resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides; polyimide resins; polyethylene resins; polypropylene resins; trimethylpentene resins; polyphenylene sulfide resins; acrylic resins; and polyvinyl alcohol resins. These resins can be used alone or in combination.
[0092] <First Impregnation Process>
[0093] In the first impregnation step (ii) of the manufacturing method of the present invention, a first conductive polymer containing liquid is impregnated into a capacitor element and dried to form a solid electrolyte precursor in the gap between the anode foil and the cathode foil (especially on the oxide coating).
[0094] The formation of the solid electrolyte precursor can be carried out, for example, by an impregnation method. That is, for instance, after filling an introductory tank with a conductive polymer-containing liquid (e.g., a dispersion with a conductive polymer compound concentration of 2% by mass), the capacitor element is immersed in the conductive polymer-containing liquid. Then, the capacitor element is removed from the introductory tank and subjected to heat treatment. This allows the solid electrolyte precursor to be introduced into the gap between the anode and cathode foils, and the solid electrolyte precursor can be formed on the oxide coating.
[0095] (The first conductive polymer compound contains liquid)
[0096] The first conductive polymer-containing liquid used in the first impregnation process is a liquid containing conductive polymers, and as an additive, it contains an organic solvent with a boiling point or decomposition temperature of 150°C or higher at a mass percentage of less than 15%.
[0097] The first conductive polymer containing liquid can be a conductive polymer dispersion or a conductive polymer solution, especially a conductive polymer dispersion.
[0098] In this invention, "organic solvent" refers to an organic compound whose monomer is liquid at room temperature (25°C), and is a compound that is different from conductive polymers and optional dopants.
[0099] The content of the first conductive polymer in the liquid can be 0.1-10% by mass, 0.2-5% by mass, and especially 0.5-3% by mass.
[0100] As a dispersion medium for conductive polymer dispersions, protic solvents such as water, alcohols (e.g., methanol, ethanol, 1-propanol, butanol), and mixtures thereof can be used. The content of the dispersion medium (especially water) in the conductive polymer dispersion can be 50–99% by mass, 55–90% by mass, or further 60–80% by mass.
[0101] As solvents for conductive polymer solutions, for example, water, alcohols (e.g., methanol, ethanol, 1-propanol, butanol), and mixtures thereof can be used.
[0102] It can also contain aromatic nitro compounds in the liquid containing conductive polymers.
[0103] (additive)
[0104] As described above, the first conductive polymer contains an organic solvent with a boiling point or decomposition temperature of 150°C or higher (especially an organic solvent with a boiling point of 150°C or higher).
[0105] Examples of organic solvents with boiling points or decomposition temperatures above 150°C include glycerol, diglycerol and polyglycerol, glycol compounds such as ethylene glycol, diethylene glycol, other polyethylene glycols and their derivatives, γ-butyrolactone, butanediol, dimethyl sulfoxide, sulfolane, N-methylpyrrolidone, dimethyl sulfolane, polyethylene glycol and their derivatives. They can be used alone or in combination of two or more.
[0106] The content of the organic solvent with a boiling point or decomposition temperature of 150°C or higher in the first conductive polymer containing liquid is 15% by mass or less. This content can be 1% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, 5% by mass or more, or 6% by mass or more, and / or can be less than 15% by mass, less than 14% by mass, less than 13% by mass, less than 12% by mass, or less than 11% by mass. This content is preferably 1 to 15% by mass, 1 to 14% by mass, more preferably 2 to 13% by mass, and particularly preferably 7 to 12% by mass. In one embodiment, the content is 1 to 10% by mass, 1 to 8% by mass, or further 2 to 6% by mass. In one embodiment, the content of the organic solvent with a boiling point or decomposition temperature of 150°C or higher in the first conductive polymer containing liquid is less than the content of the organic solvent with a boiling point or decomposition temperature of 150°C or higher in the second conductive polymer containing liquid; in this case, more desirable properties can be obtained.
[0107] Additives (organic solvents with a boiling point or decomposition temperature above 150°C) added to the conductive polymer-containing liquid can exist as a liquid substance between the anode and cathode foils after capacitor manufacturing. In this case, the conductivity of the conductive polymer compound can be further improved. Furthermore, in this case, the capacitor characteristics are sometimes improved, resulting in low ESR (low resistance), high capacitance, and a delayed degradation effect (longer lifetime) due to improved conductivity. While not intended to be theoretically limited, it is believed that when additives are present in the conductive polymer-containing liquid, absorption by the conductive polymer particles promotes the formation of the conductive polymer compound's arrangement structure, resulting in improved conductivity.
[0108] (Conductive polymer)
[0109] As a conductive polymer (conductive polymer compound), at least one selected from polythiophene, polypyrrole, and polyaniline and their derivatives can be mentioned. The conductive polymer compound can be at least one of them. Preferably, the conductive polymer compound is a polymer of EDOT and its derivatives. Particularly preferred conductive polymer compounds are polyethylene dioxythiophene (PEDOT) (especially poly(3,4-ethylenedioxythiophene)).
[0110] (Dopant)
[0111] Solid electrolytes may further contain dopants. Dopants can be polyanionic. Specific examples of dopants include aromatic sulfonic acids such as benzenesulfonic acid or its derivatives, naphthalenesulfonic acid or its derivatives, and anthraquinone sulfonic acid or its derivatives; polymeric sulfonic acids such as polystyrene sulfonic acid (PSS), sulfonated polyesters, phenol sulfonic acid phenolic varnish resins, copolymers of styrene sulfonic acid and non-sulfonic acid monomers (methacrylates, acrylates, alkoxysilane compounds containing unsaturated hydrocarbons or their hydrolysis products, etc.); and chain sulfones such as methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, and butyric acid. They can be used alone or in combination of two or more.
[0112] As for polystyrene sulfonic acid (PSS), polystyrene sulfonic acid with a weight average molecular weight of 10,000 to 1,000,000 is preferred.
[0113] In a particularly preferred embodiment, the solid electrolyte comprises polyethylene dioxythiophene (PEDOT) as a conductive polymer and polystyrene sulfonic acid (PSS) as a dopant.
[0114] (particle)
[0115] The conductive polymer in the liquid containing the conductive polymer can exist in the form of microparticles. In a preferred embodiment, the first conductive polymer containing liquid contains microparticles composed of a conductive polymer compound and optional dopants. The average particle size of the microparticles composed of the conductive polymer compound and dopants can be from 1 nm to 600 nm, preferably from 1 nm to 300 nm, or further from 5 nm to 200 nm (e.g., 20 nm). The average particle size of the microparticles composed of the conductive polymer and dopants can be determined, for example, by particle size distribution based on dynamic light scattering.
[0116] There are no particular limitations on the method for preparing conductive polymer dispersions; conventional methods can be followed. As a specific example, the preparation of PEDOT / PSS microparticle dispersions can be carried out according to the following steps (a) to (e):
[0117] (a) A PEDOT / PSS particulate dispersion (e.g., 2% by mass) was prepared using ethylene dioxythiophene (EDOT) monomer and polystyrene sulfonic acid (PSS).
[0118] (b) Remove excess cationic and / or anionic components by ion exchange treatment.
[0119] (c) Use a rotary homogenizer or an ultrasonic homogenizer for micronization.
[0120] (d) Adjust the pH to 2–5 through neutralization treatment.
[0121] (e) Adding a high-boiling-point compound to the PEDOT / PSS microparticle dispersion. This can sometimes improve conductivity.
[0122] (Solid electrolyte precursor)
[0123] As a result of the first impregnation process, a solid electrolyte precursor is formed. The solid electrolyte precursor is formed between the anode foil and the cathode foil of the capacitor element.
[0124] <Second Impregnation Process>
[0125] In the second impregnation step (iii) of the manufacturing method of the present invention, a second conductive polymer containing liquid is impregnated into a capacitor element having a solid electrolyte portion precursor obtained as a result of the first impregnation step, and then dried to form a solid electrolyte portion in the gap between the anode foil and the cathode foil (especially on the oxide coating).
[0126] For details regarding the second impregnation process, please refer to the description of the first impregnation process described above. For example, regarding the composition of the conductive polymer containing liquid, the impregnation method, the dispersion medium, the solvent, the conductive polymer, and the organic solvent with a boiling point or decomposition temperature of 150°C or higher, please refer to the description of the first impregnation process and the description of the first conductive polymer containing liquid described above.
[0127] The organic solvent containing the second conductive polymer as an additive, with a boiling point or decomposition temperature of 150°C or higher, may be the same as or different from the organic solvent containing the first conductive polymer as an additive with a boiling point or decomposition temperature of 150°C or higher.
[0128] The content of the conductive polymer in the liquid containing the second conductive polymer can be 0.1-10% by mass, 0.2-5% by mass, and especially 0.5-3% by mass.
[0129] When the second conductive polymer containing liquid is a conductive polymer dispersion, the content of the dispersion medium (especially water) in the conductive polymer dispersion can be 30-85% by mass, 40-80% by mass, or further 50-75% by mass.
[0130] The second conductive polymer containing liquid contains a conductive polymer and at least 15% by mass of an organic solvent with a boiling point or decomposition temperature of 150°C or higher. The content of the additive in the second conductive polymer containing liquid can be 15-50% by mass, further 15-45% by mass, and particularly 20-45% by mass. In one embodiment, the content exceeds 15% by mass. The content can also be 16% by mass or more, 17% by mass or more, 18% by mass or more, 19% by mass or more, 20% by mass or more, exceeding 20% by mass, 21% by mass or more, 22% by mass or more, 23% by mass or more, 24% by mass or more, 25% by mass or more, 26% by mass or more, 27% by mass or more, 28% by mass or more, 29% by mass or more, or 30% by mass or more, and / or can be less than 60% by mass, less than 58% by mass, less than 56% by mass, less than 54% by mass, less than 52% by mass, less than 50% by mass, or less than 48% by mass. In one embodiment, the content is 16-50% by mass, 18-48% by mass, 20-45% by mass, or further 30-45% by mass. In one embodiment, the content of the organic solvent with a boiling point or decomposition temperature of 150°C or higher in the liquid containing the second conductive polymer is greater than the content of the organic solvent with a boiling point or decomposition temperature of 150°C or higher in the liquid containing the first conductive polymer, and in this case, more desirable properties can be obtained.
[0131] (Solid Electrolyte Section)
[0132] As a result of the second impregnation process, a solid electrolyte section is formed. The solid electrolyte section is composed of a solid electrolyte. The solid electrolyte section contains a conductive polymer.
[0133] The solid electrolyte portion exists in the gap between the anode foil and the cathode foil. In this disclosure, the "gap between the anode foil and the cathode foil" includes not only the "gap between the anode foil and the spacer, and between the cathode foil and the spacer," but also the "gap between the fibers within the spacer." In addition, the "gap between the anode foil and the cathode foil" also includes the "gap in the etch pits (recesses) formed on the surface of the anode foil or cathode foil by roughening through etching."
[0134] The solid electrolyte portion, composed of a solid electrolyte, is at least partially in contact with an oxide coating formed on the surface of the anode foil. The solid electrolyte portion has a conductive polymer compound and optionally a dopant.
[0135] Solid electrolytes can take various forms, such as continuous, uniform thick or thin layers, films, or aggregates of particles or networks of particle chains. Solid electrolytes are particularly characterized by particle layers composed of particles containing conductive polymers (and optionally dopants).
[0136] The solid electrolyte portion is in direct contact, at least partially, with the oxide coating of the anode foil and at least partially with the metal surface and / or oxide coating of the cathode foil.
[0137] Solid electrolytes containing conductive polymers can also be formed by polymerizing monomers through a process known as "in-situ polymerization".
[0138] In the capacitor disclosed herein, the proportion of the conductive polymer compound in the gap between the anode foil and the cathode foil may be 0.5 vol% to 40 vol%, or further 1.0 vol% to 20 vol%.
[0139] <Liquid Matter>
[0140] The method disclosed herein may further include: impregnating a liquid substance between the anode foil and the cathode foil of a capacitor element having a solid electrolyte portion. In the resulting electrolytic capacitor, the liquid substance is preferably present between the anode foil and the cathode foil. The liquid substance may particularly be present in a manner that surrounds the solid electrolyte constituting the solid electrolyte portion (especially particles containing conductive polymeric compounds constituting the solid electrolyte portion).
[0141] From the perspective of coating repair, electrically neutral and polar liquid substances (solvents) are preferred. This solvent is less susceptible to repulsion caused by the surface charge of PEDOT / PSS particles, thus penetrating into the interior and moving to the outer side of the particles. Furthermore, since an oxygen-containing polar solvent can be supplied, coating formation can be achieved with high efficiency. Examples of such solvents include proton-based high-boiling-point polar solvents with boiling points of 150°C or higher, such as ethylene glycol, diethylene glycol, triethylene glycol, glycerol, and their derivatives, as well as polymer solutions of polyethylene glycol, polyalkylene glycols, polyglycerol, polyoxyalkylene polyglycerol ethers, and their derivatives.
[0142] In the capacitor disclosed herein, the proportion of liquid material in the gap between the anode foil and the cathode foil can be 10 vol% to 99 vol%, particularly 50 vol% to 99 vol%, or further 70 vol% to 99 vol%.
[0143] Liquid substances are not particularly limited, and may include organic solvents, especially high-molecular-weight organic solvents. Liquid substances may include, for example, water, hydrophilic polymers, components with hydroxyl groups such as polyoxyethylene and its derivatives (polyglycerol), water-soluble polyurethane, water-soluble polyester, water-soluble polyamide, water-soluble polyimide, water-soluble polyacrylic acid, water-soluble polyacrylamide, water-soluble organosilicon, polyvinyl alcohol, polyacrylic acid, etc., or mixtures thereof.
[0144] In particular, the components of the liquid substance include: glycol compounds such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, and other polyethylene glycols and their derivatives; glycerol and diglycerol and their derivatives; γ-butyrolactone; sulfolane; 3-methylsulfolane; 2,4-dimethylsulfolane; and dimethylformamide. One of these compounds may be used alone, or two or more may be used in combination. Ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, other polyethylene glycols and their derivatives are preferred, with ethylene glycol and diethylene glycol being the most preferred. When ethylene glycol and / or diethylene glycol are used as the liquid substance, electrolytic capacitors with particularly good reflux characteristics can be obtained.
[0145] Liquid substances are, for example, liquids capable of retaining acidic and basic components. Liquid substances, especially solvents, are capable of dissolving acidic and basic components, which are solutes, within the solvent.
[0146] In particular, the liquid substance contains a diol compound (especially ethylene glycol and / or diethylene glycol) in a total proportion of 30% to 99% by mass, 50% to 95% by mass, or further 60% to 80% by mass. Additionally, in a specific embodiment, the liquid substance contains a diol compound (especially ethylene glycol and / or diethylene glycol) in a total proportion of 90% to 100% by mass, 90% to 99.9% by mass, or further 95% to 99.5% by mass.
[0147] (water)
[0148] Liquid substances can also contain water.
[0149] When the liquid substance present in the gap between the anode foil and the cathode foil contains "water", it can achieve particularly good results in reducing the defect density and leakage current of the oxide coating.
[0150] The water content relative to the liquid substance can be 0% to 10% by mass, preferably 0.1% to 10% by mass, and more preferably 0.5% to 5% by mass. When the water content is within this range, the defect repair effect of the oxide coating can be fully obtained, and the disadvantages caused by excessive water content (such as capacitor expansion that may occur under long-term use in high-temperature environments) can be avoided or suppressed.
[0151] It should be noted that when an electrolytic capacitor contains liquid substances, it can be specifically referred to as a hybrid electrolytic capacitor.
[0152] <Liquid substance introduction process>
[0153] The method for manufacturing an electrolytic capacitor disclosed herein may optionally include a step of introducing a liquid substance into the capacitor element (particularly the gap between the anode foil and the cathode foil). For details regarding the liquid substance, please refer to the above description relating to electrolytic capacitors.
[0154] In one embodiment, a liquid substance is introduced into the capacitor element having a solid electrolyte section, thereby placing the liquid substance between the anode foil and the cathode foil.
[0155] The introduced liquid material can penetrate into the formed solid electrolyte section, thereby further improving the conductivity of the conductive polymer compound. Furthermore, in this case, the capacitor characteristics are sometimes improved, resulting in lower ESR (lower resistance), higher capacitance, and a delayed degradation effect (longer lifetime) due to improved conductivity. While not intended to be theoretically definitive, it is believed that the liquid material (e.g., high-boiling-point compounds such as ethylene glycol) penetrating into the solid electrolyte section is absorbed by the conductive polymer compound particles, thereby promoting the formation of the conductive polymer compound's arrangement structure, resulting in improved conductivity.
[0156] In this process, for example, the liquid substance 27 is introduced into the gap between the anode foil 21 and the cathode foil 23 in such a way that the liquid substance 27 surrounds the solid electrolyte and occupies a proportion in the gap of 10 vol% to 99 vol%.
[0157] When filling liquid material using the impregnation method, the capacitor element can be immersed in the liquid material after the inlet tank is filled with liquid material, thereby introducing the liquid material into the gap.
[0158] Liquid substances can contain both acidic and alkaline components.
[0159] As acidic components, organic acids and inorganic acids, as well as their complex compounds, can be listed.
[0160] Examples of organic acids include carboxylic acids, phenols, and sulfonic acids. Examples of carboxylic acids include formic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, sulfosalicylic acid, maleic acid, adipic acid, benzoic acid, methylbenzoic acid, heptanoic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcinolic acid, phloroglucinolic acid, gallic acid, and citric acid.
[0161] Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid.
[0162] Examples of compounds that are complex compounds of organic and inorganic acids include borosilicate acid, borodioxalic acid, and borodiethanolic acid.
[0163] The acid components described above can be used alone or in combination of two or more.
[0164] For example, it contains acidic components at a rate of 0.01% to 15% by mass relative to the liquid substance.
[0165] The alkali component can be selected from one or more of amines, amidines, and ammonia, with amines being preferred.
[0166] Compared to liquid substances, it can contain alkaline components at concentrations ranging from 0.01% to 15% by mass.
[0167] (Aromatic nitro compounds)
[0168] The liquid material of the electrolytic capacitor disclosed herein may contain aromatic nitro compounds. Aromatic nitro compounds are aromatic compounds containing nitro groups. By absorbing hydrogen gas generated in processes such as re-chemical conversion reactions, aromatic nitro compounds can improve the voltage withstand and heat resistance of the capacitor.
[0169] When using aromatic nitro compounds, the proportion of aromatic nitro compounds in the liquid substance can be 0.5% to 10% by mass, 0.5% to 5% by mass, or further 1% to 5% by mass.
[0170] Aromatic nitro compounds may be at least one selected from the group consisting of nitrophenol, nitroacetophenone, nitrobenzyl alcohol, nitrobenzoic acid, nitrobenzaldehyde, nitroaniline, nitrobenzene dicarboxylic acid, nitroaniline, nitroacetaniline, nitrophenylacetic acid, nitrocresol, dinitrobenzoic acid, methylnitrobenzoic acid, nitroterephthalic acid, and nitroisophthalic acid. They may be used alone or in combination of two or more.
[0171] The preferred aromatic nitro compound is at least one selected from the group consisting of nitrophenol, nitroacetophenone, nitrobenzyl alcohol, nitrobenzoic acid, and nitrobenzaldehyde. Nitroacetophenone is particularly preferred among the aromatic nitro compounds.
[0172] <Other follow-up processes>
[0173] Electrolytic capacitors can be manufactured by encapsulating capacitor elements containing a solid electrolyte (and optionally a liquid substance) produced through the above-described processes into a housing. This process (assembly / packaging process) is described exemplarily below.
[0174] In the assembly / packaging process, for example, the sealing member 40 is mounted on the capacitor element 20, and after the capacitor element 20 is inserted into the metal housing 10, the metal housing 10 is tightly fitted near the opening end of the metal housing 10. As the sealing member 40, isobutylene-isoprene rubber (IIR) can be used, for example. Alternatively, rubber materials such as ethylene-propylene-terpolymer (EPT), EPT-IIR blend rubber, silicone rubber, or rubber composite materials made by bonding rubber with resins such as phenolic resin (Bakelite), epoxy resin, or fluororesin can be used instead of isobutylene-isoprene rubber (IIR). Then, optionally, an aging process is performed by applying a specified voltage in a high-temperature atmosphere. Thus, the electrolytic capacitor 1 of the embodiment is completed.
[0175] Example
[0176] Hereinafter, embodiments of the present invention will be described in more detail with reference to examples. The following examples and comparative examples are not intended to limit the present invention.
[0177] <<Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-4>>
[0178] In Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-4, solid electrolytic capacitors were fabricated by setting the concentration of additives in the conductive polymer-containing liquid used during impregnation to various values, and the capacitor characteristics were evaluated.
[0179] (Manufacturing of solid electrolytic capacitors)
[0180] Solid electrolytic capacitors rated at 25V-330μF were manufactured by impregnating the capacitor element with a conductive polymer-containing liquid in a two-stage impregnation process.
[0181] The capacitor element is made by winding an aluminum anode foil with a voltage-resistant coating corresponding to the rated voltage of the capacitor and an aluminum cathode foil separated by a cellulose separator.
[0182] As a conductive polymer-containing liquid, an aqueous dispersion containing conductive polymer compound particles and additives comprising a total of 2.0% by mass of PEDOT and PSS was used. Commercially available reagents were used.
[0183] The materials used in the impregnation process are as follows:
[0184] • Conductive polymer: PEDOT
[0185] • Dopant: PSS
[0186] • Organic solvents with a boiling point or decomposition temperature above 150°C, used as additives: (diglycerol and polyglycerol)
[0187] Water as a dispersion medium
[0188] In Examples 1-1 to 1-2 and Comparative Examples 1-1 to 1-4, as shown in Table 1 below, a series of solid electrolytic capacitors were manufactured by setting the dosage of the second conductive polymer containing liquid used in the second impregnation to a constant (40% by mass), while the dosage of the first conductive polymer containing liquid used in the first impregnation was set to various values (4% by mass, 12% by mass, 18% by mass, 19% by mass, 20% by mass, 23% by mass).
[0189] For the obtained capacitors, the capacitance (μF) at 120 Hz and the ESR (mΩ) at 100 kHz were measured using an LCR meter. The measured values were compared with those of capacitors manufactured as described above, except that no second impregnation was performed, and the capacitance increase factor and ESR decrease factor were calculated.
[0190] The results are shown in Table 1 below and Figure 3 and Figure 4 .
[0191] The evaluation of the capacitance increase effect in Table 1 is based on the capacitance increase ratio compared to capacitors that have only undergone the first impregnation, and is conducted according to the following criteria:
[0192] (++) The capacity increase rate is more than 2.00 times.
[0193] (+) Capacity increase rate is greater than 1.10 times and less than 2.00 times.
[0194] (-) The capacity increase rate is less than 1.10 times.
[0195] The evaluation of the ESR reduction effect in Table 1 is based on the ESR reduction effect compared with the capacitor that only underwent the first impregnation, and is carried out according to the following criteria:
[0196] (+++) ESR reduction factor is below 0.40.
[0197] (++) ESR reduction ratio exceeding 0.40x and below 0.60x.
[0198] (+) ESR reduction ratio greater than 0.60x and less than 0.80x.
[0199] (-) ESR reduction rate exceeds 0.80 times.
[0200] Figure 3 The graph is plotted with the additive content of the first impregnation on the horizontal axis and the volume increase rate (in times) on the vertical axis. That is, Figure 3 This indicates the extent of volume increase achieved by the second infiltration with respect to the first added dose shown on the horizontal axis.
[0201] Figure 4 The graph is plotted with the additive content of the first impregnation on the horizontal axis and the ESR reduction rate (in times) on the vertical axis. That is, Figure 4 This indicates the extent of ESR reduction achieved with the second infiltration based on the first added dose shown on the horizontal axis.
[0202] <Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-3>
[0203] In Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-3, a series of dispersions were prepared with various additive concentrations (9% by mass, 12% by mass, 18% by mass, 19% by mass, and 20% by mass) in the conductive polymer containing liquid for the first impregnation. The additive concentration in the second conductive polymer containing liquid for the second impregnation was set to 20% by mass. Otherwise, the capacitors were manufactured and their characteristics evaluated in the same manner as in Examples 1-1, etc. The results are shown in Table 1 below. Figure 3 and Figure 4 .
[0204] <Examples 3-1 to 3-2 and Comparative Examples 3-1 to 3-2>
[0205] In Examples 3-1 to 3-2 and Comparative Examples 3-1 to 3-2, a series of dispersions were prepared with various additive concentrations (11% by mass, 15% by mass, 19% by mass, 20% by mass) in the conductive polymer containing liquid for the first impregnation. The additive concentration in the second conductive polymer containing liquid for the second impregnation was set to 15% by mass. Otherwise, the capacitors were manufactured and their characteristics evaluated in the same manner as in Example 1-1 above. The results are shown in Table 1 below. Figure 3 and Figure 4 .
[0206] <Comparative Examples 4-1 to 4-6>
[0207] In Comparative Examples 4-1 to 4-6, a series of dispersions were prepared with various additive concentrations (9% by mass, 12% by mass, 18% by mass, 19% by mass, 20% by mass, and 21% by mass) in the conductive polymer containing liquid for the first impregnation. The additive dosage in the second conductive polymer containing liquid for the second impregnation was set to 10% by mass. Otherwise, the capacitors were manufactured and their characteristics evaluated in the same manner as in Example 1-1 above. The results are shown in Table 1 below. Figure 3 and Figure 4 .
[0208] [Table 1]
[0209]
[0210] As shown in Table 1 and Figure 3 As shown, it was observed that the lower the content of the additive in the first impregnation, the greater the potential for increased capacity. Furthermore, it was found that if the content of the additive in the first impregnation exceeded 15% by mass, almost no capacity-increasing effect was observed from the second impregnation.
[0211] Additionally, as shown in Table 1 and Figure 4 As shown, it was confirmed that the higher the content of the second additive, the greater the ESR reduction effect. In particular, a particularly large ESR reduction effect was obtained when the content of the first additive was relatively low and the content of the second additive was relatively high.
[0212] Explanation of reference numerals in the attached figures
[0213] 1 Electrolytic capacitor
[0214] 10 Metal casing
[0215] 20 Capacitor Components
[0216] 21 Anode foil
[0217] 22, 24 Oxidation Coating
[0218] 23 Cathode foil
[0219] 25 Separators
[0220] 26 Solid electrolytes
[0221] 27 Liquid substances
[0222] Lead wires 29 and 30
[0223] 40 Sealing components.
Claims
1. A method for manufacturing an electrolytic capacitor, wherein, The electrolytic capacitor has an anode foil with an oxide coating formed on its surface and a cathode foil, and a solid electrolyte portion containing a conductive polymer is present in the gap between the anode foil and the cathode foil. The method includes: (i) Provides a capacitor element having an anode foil and a cathode foil having an oxide coating formed on their surfaces; (ii) Impregnating the capacitor element with a first conductive polymer containing an organic solvent with a boiling point or decomposition temperature of 150°C or higher at a content of 15% by mass or less, and drying it to form a solid electrolyte precursor in the gap between the anode foil and the cathode foil; and (iii) The capacitor element in which the solid electrolyte precursor is formed is impregnated with a liquid containing an organic solvent with a boiling point or decomposition temperature of 150°C or higher at a content of 15% by mass or more, and then dried to form a solid electrolyte in the gap between the anode foil and the cathode foil.
2. The method according to claim 1, wherein, The first conductive polymer containing liquid contains 2-15% by mass of the organic solvent with a boiling point or decomposition temperature of 150°C or higher, and / or the second conductive polymer containing liquid contains 15-45% by mass of the organic solvent with a boiling point or decomposition temperature of 150°C or higher.
3. The method according to claim 1 or 2, wherein, The second conductive polymer contains an organic solvent with a boiling point or decomposition temperature of 150°C or higher, accounting for more than 20% by mass.
4. The method according to claim 1 or 2, wherein, The organic solvent with a boiling point or decomposition temperature of 150°C or higher comprises at least one selected from glycerol, diglycerol, polyglycerol, ethylene glycol, diethylene glycol, polyethylene glycol, and their derivatives.
5. The method according to claim 1 or 2, wherein, The content of conductive polymer in the first conductive polymer containing liquid and the second conductive polymer containing liquid is 0.5 to 5% by mass, respectively.
6. The method according to claim 1 or 2, wherein, The conductive polymer contained in the first conductive polymer containing liquid and the second conductive polymer containing liquid is polythiophene and its derivatives.
7. The method according to claim 1 or 2, wherein, Both the first conductive polymer containing liquid and the second conductive polymer containing liquid contain microparticles composed of conductive polymer compounds and optional dopants.
8. The method according to claim 7, wherein, The dopant is polystyrene sulfonic acid.
9. The method according to claim 1 or 2, wherein, The electrolytic capacitor is a solid electrolytic capacitor.
10. The method according to claim 1 or 2, further comprising: A liquid substance is impregnated between the anode foil and the cathode foil of the capacitor element having the solid electrolyte section.
Citation Information
Patent Citations
Production of solid electrolytic capacitor
JP1997213575A
Method for manufacturing capacitor
JP2010087401A
Method for manufacturing electrolytic capacitor
JP2014082392A